UJI PENGEMBANGAN Spora ENTOMOPATOGEN BUNGA ENTOMOPATOGEN Lecanicillium lecanii MENGGUNAKAN HAEMOCYTOMETER - Indah Nuzulul Rohmah; Trisnan Alif (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Lecanicillium lecanii is one type of entomopathogenic fungus that can infect several insects with very variable mortality rates. control solutions using biological agents of entomopathogenic fungi are able to have a good impact and are environmentally friendly. The writing of this study used both primary and secondary data collection methods carried out by observation and quantitative analysis techniques, in the form of observations, explanations of the data obtained, and carrying out the activities related to the spore density test of the entomopathogenic fungus L. lecanii using a haemocytometer at PTPH Coordinator Office for Bojonegoro Region. The results of the spore density test of the entomopathogenic fungus L. lecanii were 6.05×107, which was carried out using rice solid media and potato liquid media for propagation and calculated using a haemocytometer and observed using a binocular microscope with a magnification of 400×. The results of the density test are classified as good quality and able to be applied to plants by farmers to control a pest or Plant Pest Organisms.